2006
DOI: 10.1016/j.cmet.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Hypomorphic mutation of PGC-1β causes mitochondrial dysfunction and liver insulin resistance

Abstract: PGC-1beta is a transcriptional coactivator that potently stimulates mitochondrial biogenesis and respiration of cells. Here, we have generated mice lacking exons 3 to 4 of the Pgc-1beta gene (Pgc-1beta(E3,4-/E3,4-) mice). These mice express a mutant protein that has reduced coactivation activity on a subset of transcription factors, including ERRalpha, a major target of PGC-1beta in the induction of mitochondrial gene expression. The mutant mice have reduced expression of OXPHOS genes and mitochondrial dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
123
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(132 citation statements)
references
References 44 publications
8
123
1
Order By: Relevance
“…Importantly, it has been shown that pharmacological and genetic manipulations that alleviate oxidative stress lead to improvements in insulin sensitivity [10][11][12]. PGC-1α and PGC-1β have both been shown to regulate the production of a range of antioxidant proteins in a variety of cells [14][15][16]. Consistent with these reports, we observed a robust increase in the protein levels of SOD-1 and SOD-2 and in glutathione peroxidase activity in response to Pgc-1β overexpression in muscle.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Importantly, it has been shown that pharmacological and genetic manipulations that alleviate oxidative stress lead to improvements in insulin sensitivity [10][11][12]. PGC-1α and PGC-1β have both been shown to regulate the production of a range of antioxidant proteins in a variety of cells [14][15][16]. Consistent with these reports, we observed a robust increase in the protein levels of SOD-1 and SOD-2 and in glutathione peroxidase activity in response to Pgc-1β overexpression in muscle.…”
Section: Discussionsupporting
confidence: 80%
“…We observed that overexpression of Pgc-1β was able to drive a transcriptional programme that increased the capacity for mitochondrial substrate oxidation, improved antioxidant defences and partially protected against HFD-induced insulin resistance. Gain-and loss-of-function studies have shown that PGC-1β regulates the expression of genes involved in mitochondrial function and lipid metabolism [15,16,38,39]. However, although much is known about the physiological stimuli that increase PGC-1α content in muscle, the in vivo regulation of PGC-1β is less well understood.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…On the other hand, PGC1β expression also potentiates oxygen consumption with increased mitochondrial DNA copies and intracellular ATP levels. This can be explained because PGC1β is the coactivator of NRF1; it binds and activates mitochondrial transcription factor A (mtTFA) (Lelliott et al ., 2006; Vianna et al ., 2006), which directly regulates mitochondrial DNA replication (Wu et al ., 1999). In addition, we show that PGC1β expression slightly increases ROS formation in MM cells (Gomez de Cedron et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%